Risk factors associated with human echinococcosis: a systematic review and meta-analysis - Kakamad, Fahmi H.; Anwar, Khanda A.; Ahmed, Harem K.; Habibullah, Imad J.; Kaka Ali, Hemn H.; Nasralla, Hawkar A.; Abdullah, Hiwa O.; Tahir, Soran H.; Kareem, Honar O.; Hasan, Ali H.; Gharib, Dana T.; Asaad, Hoshmand R.; et al. (Frontiers in Veterinary Science, 2024)
IntroductionEchinococcosis is a widespread zoonotic disease caused by tapeworms of the Echinococcus genus, manifesting in mature or larval forms. Cystic echinococcosis (CE) and alveolar echinococcosis (AE) are the primary types affecting humans, linked, respectively, to Echinococcus granulosus and Echinococcus multilocularis. This study is a systematic review and meta-analysis of the risk factors associated with CE and AE in humans.MethodsRelevant English publications were found through a thorough search of eligible databases. The inclusion criteria focused on cross-sectional and case–control studies investigating risk factors for human echinococcosis. Collected data included author, country, study design, demographics, sample size, literacy, occupation, drinking water source, dog ownership, and hand hygiene.ResultsA total of 1,594 studies were found in the initial search, with only 36 papers (involving 1,207,436 cases) meeting the inclusion criteria. Most of the study population (99.35%) showed no echinococcosis infection, while 0.65% were infected. Of the infected cases, 77.92% had CE, while 22.08% had AE. Among 629,996 (52.18%) females, 4,830 (0.76%) were infected, compared to 2,968 (0.52%) infections among 565,872 (46.86%) males (p < 0.001). Rural areas, low education levels, agricultural/livestock workers, dog owners, water sources, and poor hand hygiene were all significantly associated with the infection (p < 0.05).ConclusionEchinococcosis remains a global health concern, particularly among rural residents, those with lower education, agricultural workers, and dog owners. Targeted public health measures, including improved hygiene practices and access to clean water, are essential to reducing its impact.